Diabetes Prevention and Care Capacity at Urban Indian Health Organizations - Fort, Meredith P.; Reid, Margaret; Russell, Jenn; Santos, Cornelia J.; Running Bear, Ursula; Begay, Rene L.; Smith, Savannah L.; Morrato, Elaine H.; Manson, Spero M. (Frontiers in Public Health, 2021)
American Indian and Alaska Native (AI/AN) people suffer a disproportionate burden of diabetes and cardiovascular disease. Urban Indian Health Organizations (UIHOs) are an important source of diabetes services for urban AI/AN people. Two evidence-based interventions—diabetes prevention (DP) and healthy heart (HH)–have been implemented and evaluated primarily in rural, reservation settings. This work examines the capacity, challenges and strengths of UIHOs in implementing diabetes programs. Methods: We applied an original survey, supplemented with publicly-available data, to assess eight organizational capacity domains, strengths and challenges of UIHOs with respect to diabetes prevention and care. We summarized and compared (Fisher's and Kruskal-Wallis exact tests) items in each organizational capacity domain for DP and HH implementers vs. non-implementers and conducted a thematic analysis of strengths and challenges. Results: Of the 33 UIHOs providing services in 2017, individuals from 30 sites (91% of UIHOs) replied to the survey. Eight UIHOs (27%) had participated in either DP (n = 6) or HH (n = 2). Implementers reported having more staff than non-implementers (117.0 vs. 53.5; p = 0.02). Implementers had larger budgets, ~$10 million of total revenue compared to $2.5 million for non-implementers (p = 0.01). UIHO strengths included: physical infrastructure, dedicated leadership and staff, and community relationships. Areas to strengthen included: staff training and retention, ensuring sufficient and consistent funding, and data infrastructure. Conclusions: Strengthening UIHOs across organizational capacity domains will be important for implementing evidence-based diabetes interventions, increasing their uptake, and sustaining these interventions for AI/AN people living in urban areas of the U.S.